Manajemen Sistem Informasi Dalam Pelayanan Perizinan; Studi Kasus Di Badan Pelayanan Perizinan Terpadu Pemerintah Kota Bandung - Dayat Hidayat; Muhammad Afif Muttaqin (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2012)
Information system is an effective media in disseminating information in the modern era. Utilization of information systems in government considered to be essential to improve public services in this licensing service in Bandung city. Therefore this study aims to determine the Management Information System conducted by the Government Licensing Service Agency of Bandung (BPPT). Indicators used include three elements: planning, organizing, and supervision. The focus of this research is BPPT. The approach conducted in this study is a qualitative in order to avoid generalize the results, Data collection techniques used is the study of documentation and interviews. Based on these results, it is known that the existence of an information system that can be accessed by people in the BPPT is available with a variety of categories, and tailored to the needs and accessibility, As for management it has been well planned, but at this stage of implementation and supervision, there are still some obstacles.